Lactobacillus sakei suppresses collagen-induced arthritis and modulates the differentiation of T helper 17 cells and regulatory B cells - Jooyeon Jhun (Journal of Translational Medicine, 2020)
Abstract Background To evaluate the immunomodulatory effect of Lactobacillus sakei in a mouse model of rheumatoid arthritis (RA) and in human immune cells. Methods We evaluated whether L. sakei reduced the severity of collagen-induced arthritis (CIA) and modulated interleukin (IL)-17 and IL-10 levels, as well as whether it affected the differentiation of CD4+ T cells and regulatory B cells. We evaluated osteoclastogenesis after culturing bone marrow-derived mononuclear cells with L. sakei. Results The differentiation of T helper 17 cells and the serum level of IL-17 were suppressed by L. sakei in both human peripheral blood mononuclear cells and mouse splenocytes. The serum level of IL-10 was significantly increased in the L. sakei-treated group, whereas the regulatory T cell population was unchanged. The population of regulatory B cells significantly increased the in L. sakei-treated group. Oral administration of L. sakei reduced the arthritis incidence and score in mice with CIA. Finally, osteoclastogenesis and the mRNA levels of osteoclast-related genes were suppressed in the L. sakei-treated group. Conclusion L. sakei exerted an anti-inflammatory effect in an animal model of RA, regulated Th17 and regulatory B cell differentiation, and suppressed osteoclastogenesis. Our findings suggest that L. sakei has therapeutic potential for RA.